Assess the policy to raise fuel prices in the local market within the framework of the Saudi economic reform plans - Al - Amin, Yousef Mohammed (Journal of Economic, Administrative and Legal Sciences, 2018)
The present study was attempt to investigate the impact of the pricing policies of petroleum products, especially fuel (gasoline and diesel oil), on their local consumption rates implied in the economic reform plans. It utilized the historical, analytical descriptive, and inductive methods. Results revealed that there was an increasing local consumption rate of petroleum products, especially fuel that may be catastrophic in the short term. The continuous oil subsidization to maintain social security network led to such high inflation in the Saudi local market and lack of allocating the subsidization to the poor resulted in the maximized benefit of the rich. Additionally, there was a dramatic increase in the number of vehicles that caused an increase in the local market and the environmental pollution. The study recommended taking planned actions to control the big demand for petroleum products, especially gasoline and diesel oil, in the Saudi local market. It concluded that a plan shall be made to adjust the pricing policy of fuel, reflecting its production costs to rationalize consumption and not to affect the competition of the economic sectors. Furthermore, a subsidization shall be allocated for the low- income population in order not to increase the unreasonable cost of living due to adjusting fuel prices.
Keywords: price; fuel; local market; planning; Saudi economy